Design of experiments on the effects of linear and hyperelastic constitutive models and geometric parameters on polymer electrolyte fuel cell mechanical and electrical behaviour. (14th April 2021) - Charbonné, C.; Dhuitte, M.-L.; Bouziane, K.; Chamoret, D.; Candusso, D.; Meyer, Y.
Abstract: In this work, the influence of the geometric and mechanical properties of the constitutive layers of a Proton Exchange Membrane Fuel Cell (PEMFC) on the system performance was investigated. More specifically, this study focused on the internal electrical resistances due to the interlayer mechanical contacts. Indeed, electrical contact resistances are one of the main sources of ohmic losses in a PEMFC and therefore require special attention to improve the system efficiency. To this end, a Design of Experiments associated with a 2D Finite Element Model including contact friction was developed and used. The typology (linear or hyperelastic) of the constitutive law of a Gas Diffusion Layer (GDL) and the layer thicknesses were parametrized and investigated. The analysis of the results shows that the impact of thicknesses and thickness ratios on PEMFC performance is more important than the typology of the GDL constitutive law. Highlights: A 2D finite element model of a single fuel cell with contact friction is developed. A hyperelastic experimental constitutive law of the GDL used is implemented. Optimal set of geometric and mechanical parameters is determined with a DoE. The ratios between the component thicknesses influence the computation stability. Performances are more impacted by layer thicknesses than by GDL constitutive law.